2018
DOI: 10.1111/1467-8500.12284
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Re‐Entry Process of Returnee Government Scholars in an Emerging Transition Economy – An Embeddedness Perspective

Abstract: This paper reports the findings of a study that investigates the factors affecting the re‐entry and readjustment process of returnee government scholars in Vietnam. These returnee scholars were originally sent overseas to study as part of changes introduced by the Vietnamese government to develop its domestic talent pool. Using the perspective of home country embeddedness, we find that career and community embeddedness factors, together with readjustment factors, have an effect on returnee scholars’ career and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 69 publications
(110 reference statements)
0
16
0
Order By: Relevance
“…Given the fact that the returnees had been exposed to the foreign research culture for a considerable amount of time and had acquired important research skills, the returning adjustment period could be long and complex (Le and LaCost, 2017). It is critical to support returnees to transition back into home conditions because a negative experience of returning is likely to prompt re-expatriation (Ho et al, 2016(Ho et al, , 2017. The equally important task is not only to attract more Vietnamese overseas-trained returnees, but also to motivate them to stay, work and make contributions in Vietnam (Tran and Marginson, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that the returnees had been exposed to the foreign research culture for a considerable amount of time and had acquired important research skills, the returning adjustment period could be long and complex (Le and LaCost, 2017). It is critical to support returnees to transition back into home conditions because a negative experience of returning is likely to prompt re-expatriation (Ho et al, 2016(Ho et al, , 2017. The equally important task is not only to attract more Vietnamese overseas-trained returnees, but also to motivate them to stay, work and make contributions in Vietnam (Tran and Marginson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Pham (2019) examined the transfer of knowledge and contributions of Vietnamese students returning home from overseas education. Ho et al (2016Ho et al ( , 2017 identified factors that impacted upon the Vietnamese returnees' intention to leave Vietnam again, but not their actual returning experiences. The Vietnamese returnees in these latter studies were those who returned from studying or working abroad.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study conducted by Ho et al (2018) have suggested that there is a need for further research about the re-expatriation of human capital after returning to home country. A need for further research is required to study the factors that might influence their intention to re-expatriate.…”
Section: R M B Rmentioning
confidence: 99%
“…The focus on factors likely to impact on ‘employee's resistance to change is important because past research has identified it as one of the main factors inhibiting successful change outcomes (Tummers , Tummers and Bekkers ). For example, Ho et al () quantitatively examine the importance of career and community‐based embeddedness on the ability to re‐adjust for Vietnamese returnees deciding whether to stay or leave Vietnam. This is important because human capital is the key to transforming these economies, and the findings show that the more embedded employees are in their community through family and friends networks, the more likely that they have high life satisfaction, which tends to encourages them to keep their expertise in the country.…”
Section: Focus Of Researchmentioning
confidence: 99%